(untitled) (Bioresearch Communications, 2021)
Intermittent fasting (IF) has two broad types: wet (with water) and dry (without water) fasting. Studies suggest that both are effective for reducing weight and for promoting overall metabolic well-being; however, their relative efficacy is not yet established. The study was a 9-day cross-over clinical trial with the purpose to compare the effectiveness of wet and dry fasting. Adult overweight women (n = 18) from Dhaka, Bangladesh were recruited as subjects of this study. It included 3 days of wet IF and 3 days of dry IF (14 h fasting and 50% calorie restriction), with a 3-day washout period (ad libitum intake) in between. Both types of IF resulted in significant weight loss. The loss was significantly higher after 3 days of dry IF (−0.23 ± 0.02 kg; P < 0.05). Waist circumference and BMI were significantly reduced in both interventions (P <0.05) and diastolic pressure changed significantly after dry fasting (P <0.05). None of the biochemical parameters (total cholesterol, triglycerides, HDL-C, LDL-C, atherogenic coefficient, and fasting plasma glucose) changed significantly within or between interventions. The intervention compliance percentage was high for both, with no significant difference. The study findings suggest that both wet and dry IF were effective for weight loss but dry IF was more effective. The biochemical parameters did not change significantly in short term and so longer trials are needed. [Trial registration number: UMIN000041481] Bioresearch Commu. 8(1): 1053-1060, 2022 (January)